MEMPERKASAKAN ORANG MELAYU DI KUBANG PASU,KEDAR MELALUI PROGRAM INDUSTRI KECIL DAN SEDERHANA (IKS) - Nursuhana, Hashim (Universiti Malaysia Sarawak(UNIMAS), 2013)
Small and Medium Enterprise (SME) is one of development approaches developed by the government to help the people, especially the Malays to be actively involved in the business. In addition, SME was created to help Malays to improve their socioecomic situation and empower. SMEs in Kedah was under Kedah Regional Development Authority (KEDA). KEDA functions to develop communities in Kubang Pasu. Even so, the Malays are still less involved in business and are still focused on small-scale entrepreneur. Therefore, this study was to investigate what programs provided by SMEs to the Malays, how the Malays accept the SME program and how the programs help to improve their socioeconomic status. The purpose of this study is to examine SMEs programme help to empower the Malays to be involved in business thereby improving their socioecomic status. This study utilise qualitative methods to gather data. 11 respondents, from various business backgrounds in Kubang Pasu, were selected to be my respondents. Respondent were selected using “snowball” technique. The findings indicate that programmed offered by SME do help to empower the Malays in improving their socioecomic status.